2013
DOI: 10.1111/eff.12037
|View full text |Cite
|
Sign up to set email alerts
|

Downstream drift of round goby (Neogobius melanostomus) and tubenose goby (Proterorhinus semilunaris) in their non‐native area

Abstract: Several Ponto‐Caspian gobiid species have recently expanded their ranges in Europe and North America. This is the first study to demonstrate passive downstream dispersal (drift) of the round goby (Neogobius melanostomus) and tubenose goby (Proterorhinus semilunaris) in newly colonised areas (River Dyje, Danube basin), a factor that could play an important role in their dispersal. Drift duration (i.e. number of dates on which the species was caught) in round goby was longer than that of both native species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…This assumption, however, may be too simplified. The increase in DD after dusk is well supported from previous studies (Pavlov et al, 1978;Brown & Armstrong, 1985;Zitek et al, 2004a;Janáč et al, 2013). It appears though that the onset und duration of drift activities during the night is variable and is likely dependent on local factors such as turbidity and others (Pavlov, 1994).…”
Section: Temporal Distribution and Sizesupporting
confidence: 89%
See 4 more Smart Citations
“…This assumption, however, may be too simplified. The increase in DD after dusk is well supported from previous studies (Pavlov et al, 1978;Brown & Armstrong, 1985;Zitek et al, 2004a;Janáč et al, 2013). It appears though that the onset und duration of drift activities during the night is variable and is likely dependent on local factors such as turbidity and others (Pavlov, 1994).…”
Section: Temporal Distribution and Sizesupporting
confidence: 89%
“…Note that the total number of individuals is lower than in Table 3, because size measurement was not possible for all specimens Hydrobiologia (2016) 781:199-216 209 This may lead to an advantage of gobiids over most native fishes which inhabit similar habitats and could be one explanation for their high invasive success. Janáč et al (2013) found a similar multimodal and prolonged seasonal pattern of Neogobius in the River Dyje (Czech Republic, Danube Basin), although with a later onset of drift activity. The seasonality of drift intensity found in Proterorhinus matches only partially with other studies.…”
Section: Temporal Distribution and Sizementioning
confidence: 61%
See 3 more Smart Citations